Vital Signs: Trends in Reported Vectorborne Disease Cases - United States and Territories, 2004-2016. - Rosenberg, Ronald; Lindsey, Nicole P.; Fischer, Marc; Gregory, Christopher J.; Hinckley, Alison F.; Mead, Paul S.; Paz-Bailey, Gabriela; Waterman, Stephen H.; Drexler, Naomi A.; Kersh, Gilbert J.; Hooks, Holley; Partridge, Susanna K.; et al. (MMWR: Morbidity & Mortality Weekly Report, 2018)
Introduction: Vectorborne diseases are major causes of death and illness worldwide. In the United States, the most common vectorborne pathogens are transmitted by ticks or mosquitoes, including those causing Lyme disease; Rocky Mountain spotted fever; and West Nile, dengue, and Zika virus diseases. This report examines trends in occurrence of nationally reportable vectorborne diseases during 2004-2016.Methods: Data reported to the National Notifiable Diseases Surveillance System for 16 notifiable vectorborne diseases during 2004-2016 were analyzed; findings were tabulated by disease, vector type, location, and year.Results: A total 642,602 cases were reported. The number of annual reports of tickborne bacterial and protozoan diseases more than doubled during this period, from >22,000 in 2004 to >48,000 in 2016. Lyme disease accounted for 82% of all tickborne disease reports during 2004-2016. The occurrence of mosquitoborne diseases was marked by virus epidemics. Transmission in Puerto Rico, the U.S. Virgin Islands, and American Samoa accounted for most reports of dengue, chikungunya, and Zika virus diseases; West Nile virus was endemic, and periodically epidemic, in the continental United States.Conclusions and Implications For Public Health Practice: Vectorborne diseases are a large and growing public health problem in the United States, characterized by geographic specificity and frequent pathogen emergence and introduction. Differences in distribution and transmission dynamics of tickborne and mosquitoborne diseases are often rooted in biologic differences of the vectors. To effectively reduce transmission and respond to outbreaks will require major national improvement of surveillance, diagnostics, reporting, and vector control, as well as new tools, including vaccines.